Factors influencing women's decision-making regarding complementary medicine product use in pregnancy and lactation - Larisa Ariadne Justine Barnes; Lesley Barclay; Kirsten McCaffery; Parisa Aslani (BMC, 2019)
Abstract Background The prevalence of complementary medicine product (CMP) use by pregnant or breastfeeding Australian mothers is high, however, there is limited data on factors influencing women's decision-making to use CMPs. This study explored and described the factors influencing women's decisions take a CMP when pregnant or breastfeeding. Methods Qualitative in-depth interviews and focus group discussions were held with 25 pregnant and/or breastfeeding women who currently used CMPs. Participants' health literacy was assessed using a validated single-item health literacy screening question and the Newest Vital Sign. Interview and focus group discussions were audio-recorded, transcribed verbatim and thematically analysed. Results Participants were a homogenous group. Most had higher education, medium to high incomes and high health literacy skills. They actively sought information from multiple sources and used a reiterative collation and assessment process. Their decision-making to take or not to take CMPs was informed by the need to establish the safety of the CMPs, as well as possible benefits or harms to their baby's or their own health that could result from taking a CMP. Their specific information needs included the desire to access comprehensive, consistent, clear, easy to understand, and evidence-based information. Women preferred to access information from reputable sources, namely, their trusted health care practitioners, and information linked to government or hospital websites and published research. A lack of comprehensive, clear, consistent, or evidence-based information often led to decisions not to take a CMP, as they felt unable to adequately establish its safety or benefits. Conversely, when the participants felt the CMPs information they collected was good quality and from reputable sources, it reassured them of the safety of the CMP in pregnancy and/or breastfeeding. If this confirmed a clear benefit to their baby or themselves, they were more likely to decide to take a CMP. Conclusions The participants' demographic profile confirms previous research concerning Australian women who use CMPs during pregnancy and lactation. Participants' high health literacy skills led them to engage in a reiterative, information-seeking and analysis process fuelled by the need to find clear information before making the decision to take, or not to take, a CMP.